Deployable, shape memory carbon fibre composites without shape memory constituents. (16th June 2017) - Robinson, Paul; Bismarck, Alexander; Zhang, Bohao; Maples, Henry A.
Abstract: Trials have been conducted to investigate the shape memory capability of an interleaved composite consisting of carbon fibre reinforced epoxy laminae and polystyrene interleaf layers. It has been shown that the composite can be readily re-shaped by deforming it at an elevated temperature and then cooling the composite in the deformed state. On re-heating, the composite almost fully returns to its original shape. One potential application of the shape memory capability of the interleaved composite is in deployable structures and a simple structure has been manufactured to demonstrate this possibility.